Evaluation of the Antimicrobial Peptide, RP557, for the Broad-Spectrum Treatment of Wound Pathogens and Biofilm - Woodburn, Kathryn Wynne; Jaynes, Jesse M.; Clemens, L. Edward (Frontiers in Microbiology, 2019)
The relentless growth of multidrug resistance and generation of recalcitrant biofilm are major obstacles in treating wounds, particularly in austere military environments where broad-spectrum pathogen coverage is needed. Designed antimicrobial peptides (dAMPs) are constructed analogs of naturally occurring AMPs that provide the first line of defense in many organisms. RP557 is a dAMP resulting from iterative rational chemical structural analoging with endogenous AMPs, human cathelicidin LL-37 and Tachyplesin 1 and the synthetic D2A21 used as structural benchmarks. RP557 possesses broad spectrum activity against Gram-positive and Gram-negative bacteria and fungi, including recalcitrant biofilm with substantial selective killing over bacterial cells compared to mammalian cells. RP557 did not induce resistance following chronic passages of P. aeruginosa and S. aureus at subinhibitory concentrations, whereas concurrently run conventional antibiotics, gentamycin and clindamycin, did. Furthermore, RP557 was able to subsequently eliminate the generated gentamycin resistant P. aeruginosa and clindamycin resistant S. aureus strains without requiring an increase in minimum inhibitory concentration (MIC) concentrations. RP557 was evaluated further in a MRSA murine wound abrasion infection model with a topical application of 0.2% RP557, completely eliminating infection. If these preclinical results are translated into the clinical setting, RP557 may become crucial for the empirical broad-spectrum treatment of wound pathogens, so that infections can be reduced to a preventable complication of combat-related injuries.